The communicative function of adjective-noun order in English. Issue 3 (2nd July 2020) - Hesseltine, Kelli; Davis, Joseph
Abstract : The problem undertaken here is to account for the relational placement in English of words traditionally known as adjectives and nouns. Two distinct orders are examined as signals of discrete meanings: one where the characterizing word is preposed to the characterized word, as in long hair, and the other where it is postposed, as in hair long . Distribution of the two signals in attested text is accounted for under the hypothesis that an Assertion of Characterization is made weaker or stronger, respectively, through this word order. With these meanings, a writer draws a distinction between Characterization the writer assumes the reader will receive as uncontested and so requires weaker Assertion and Characterization which is selected out of an array of particularly relevant possibilities and so requires stronger Assertion.